ANALISIS KOMPETENSI GURU DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR DENGAN MODERASI GAYA BELAJAR SISWA - Pradja, Novi Satria; Tresnawati, Nina; Khairudin, Fajar; Febriyana, Agung (Equilibrium: Jurnal Penelitian Pendidikan dan Ekonomi, 2023)
AbstractThe purpose of this study was to describe teacher competence, student motivation, student learning styles and student learning outcomes, the effect of teacher competence on student learning outcomes, the effect of student learning motivation on student learning outcomes, the influence of student learning styles on student learning outcomes, moderation student learning styles on the influence of teacher competence on student learning outcomes, moderation of student learning styles on the effect of student motivation on student learning outcomes. This research was conducted because the average odd semester final exam scores for economics subjects can be said to be still low, also considering the importance of student learning outcomes obtained because they are closely related to learning achievement, therefore teachers feel the need to master teacher competence, know student learning styles and arousing student motivation. The research method used is survey method. The research was conducted on students of SMP Negeri 4 Kuningan Regency using a questionnaire instrument. Data analysis will use multiple regression with the help of SPSS 24. The findings of this study: 1) the description of learning outcomes, teacher competence, learning motivation and learning styles are in the high category. 2) teacher competence has a significant effect on student learning outcomes. 3) learning motivation has a significant effect on student learning outcomes. 4) learning styles have a significant effect on student learning outcomes. 5) learning style significantly moderates the influence of teacher competence on student learning outcomes. 6) learning style moderates the influence of learning motivation on student learning outcomes significantly.Keywords: Teacher competence; learning motivation; learning styles;learning outcomes. AbstrakTujuan dari penelitian ini adalah untuk mengetahui gambaran kompetensi guru, motivasi belajar siswa, gaya belajar siswa dan hasil belajar siswa, pengaruh kompetensi guru terhadap hasil belajar siswa, pengaruh motivasi belajar siswa terhadap hasil belajar siswa, pengaruh gaya belajar siswa terhadap hasil belajar siswa, moderasi gaya belajar siswa pada pengaruh kompetensi guru terhadap hasil belajar siswa, moderasi gaya belajar siswa pada pengaruh motivasi belajar siswa terhadap hasil belajar siswa. Penelitian ini dilakukan karena melihat rata-rata nilai ujian akhir semester ganjil untuk mata pelajaran ekonomi dapat dikatakan masih rendah, juga mengingat pentingnya hasil belajar siswayang didapatkan karena erat kaitannyya dengan prestasi belajar, karena itu guru dirasa perlu menguasai kompetensi guru, mengetahui gaya belajar siswa dan membangkitkan motivasi belajar siswa. Metode penelitian yang digunakan yaitu metode survey. Penelitian dilakukan pada siswa SMP Negeri 4 Kabupaten Kuningan dengan menggunakan instrumen angket. Analisis data akan menggunakan regresi multifle dengan bantuan SPSS 24. Temuan penelitian ini:1) gambaran hasil belajar, kompetensi guru, motivasi belajar dan gaya belajar berada pada kategori tinggi. 2) kompetensi guru berpengaruh signifikan terhadap hasil belajar siswa.3) motivasi belajar berpengaruh signifikan terhadap hasil belajar siswa. 4) gaya belajar berpengaruh signifikan terhadap hasil belajar siswa. 5) gaya belajar memoderasi pengaruh kompetensi guru terhadap hasil belajar siswa secara signifikan. 6) gaya belajar memoderasi pengaruh motivasi belajar terhadap hasil belajar siswa secara signifikan. Kata kunci: Kompetensi guru; motivasi belajar; gaya belajar; hasil belajar.